ESTABLISHMENT OF GENDER-INCLUSIVE COCONUT-BASED MULTI-STOREY FARM MODEL IN BUKIDNON, PHILIPPINES - Vences C Valleser; Agripina R Aradilla; Ma Stella M Paulican (Agricultural Socio-Economics Journal, 2020)
Coconut palms are ideal for diversified (i.e. multi-storey cropping) production system across stages of growth and development. However, local information on the role of women in coconut-based multi-storey cropping is not available. Hence, this study was conceptualized to evaluate the growth of intercrops to coconut at initial vegetative growth with a woman as maintainer in a multi-storey farm in Bukidnon, Philippines. Land resource utilization in newly established coconut plantation was maximized by planting high-value intercrops such as pineapple, cacao and vegetables and were found to have no adverse effects on the growth. Eggplant as intercrop produced the highest gross income for a one-hectare non-bearing stage of coconut. On the other hand, the role of women in the establishment of a coconut-based multi-storey farm was found to be essential in all aspects of intercultural management practices, except foliar application of synthetic fertilizers and pesticides. The results could serve as guide to policy makers in establishing a gender-inclusive coconut-based multi-storey farm.